Liquidity and performance of actively managed equity funds - Fang, Rong (2011)
Most scholars have concluded that actively managed equity mutual funds as a whole underperform their passively managed counterparts, linked to some benchmarks. In other words, active equity fund managers on average do not have enough significant stock-picking abilities to add value for investors. However, earlier investigations may be flawed through failure to give adequate consideration to liquidity. Hence, this research pays much attention to liquidity effects on mutual fund performance and argues that it is a preference for holding highly liquid stocks which results in the perceived underperformance.